Application of MC-ICPMS to the precise determination of tellurium isotope compositions in chondrites, iron meteorites and sulfides - Fehr, M; Rehkamper, M; Halliday, A (2004)
New mass spectrometric techniques have been developed for the precise and accurate determination of Te isotope compositions. The methods are suitable for the analysis of stony and iron meteorites as well as sulfide mineral separates, such that they can be applied to search for Te isotope anomalies in various solar system materials. Tellurium is first separated from its matrix with a two-stage liquid chromatographic procedure. For iron meteorites, solvent-extraction is used to isolate Te from Fe prior to the column separation. The isotope composition of Te is then determined by multiple-collector inductively coupled plasma-mass spectrometry (MC-ICPMS). Tellurium has a very high first ionization potential and thus MC-ICPMS is much more suitable for the isotopic analyses than positive ion thermal ionization mass spectrometry (TIMS). Only about 100ng Te are required for a single high precision measurement. Analyses of two terrestrial sulfides, the carbonaceous chondrite Allende and the iron meteorite Canyon Diablo reveal that these have Te isotope compositions that are identical to the terrestrial standard within uncertainty. The Te isotope data acquired for standard solutions as well as meteorites and sulfides display reproducibilities (2σ) of approximately ±4500ppm for 120Te/128Te, ±140ppm for 122Te/ 128Te, ±100ppm for 124Te/128Te, ±30ppm for 126Te/128Te, and ±60ppm for 130Te/128Te. Compared to published results for meteorite samples obtained by TIMS, this represents an improvement in precision of about one to two orders of magnitude for 122-130Te/128Te and by a factor of 4 for 120Te/128Te. A number of experiments furthermore demonstrate that the isotope data acquired by MC-ICPMS are accurate, even for complex geological samples. © 2003 Elsevier B.V. All rights reserved.